Membangun kebiasaan sehat sejak dini dengan perilaku hidup bersih dan sehat (PHBS) pada anak di Sanggar Belajar Penang, Malaysia - Yanuan Ben Olina; Nury Sukraeny; Dwi Saftantri (Jurnal Surya Masyarakat, 2025)
The development of clean and healthy lifestyle behaviors (PHBS) from an early age is essential for a child's growth. This community service activity, conducted at Sanggar Belajar Penang, Malaysia, aimed to provide education on PHBS and encourage healthy habits in children. Seventeen children aged 6 to 11 years participated in the activity, which included material presentations, handwashing demonstrations, and education on healthy eating habits. The results showed that children could understand and practice proper hygiene and health behaviors. This activity underscores the importance of continuous education in PHBS and recommends further engagement with parents to ensure sustainability